Visual Stimulation Activates ERK in Synaptic and Somatic Compartments of Rat Cortical Neurons with Parallel Kinetics - Boggio, Elena M. (Public Library of Science, 2007)
BACKGROUND: Extracellular signal-regulated kinase (ERK) signalling pathway plays a crucial role in regulating diverse neuronal processes, such as cell proliferation and differentiation, and long-term synaptic plasticity. However, a detailed understanding of the action of ERK in neurons is made difficult by the lack of knowledge about its subcellular localization in response to physiological stimuli. To address this issue, we have studied the effect of visual stimulation in vivo of dark-reared rats on the spatial-temporal dynamics of ERK activation in pyramidal neurons of the visual cortex. METHODOLOGY/PRINCIPAL FINDINGS: Using immunogold electron microscopy, we show that phosphorylated ERK (pERK) is present in dendritic spines, both at synaptic and non-synaptic plasma membrane domains. Moreover, pERK is also detected in presynaptic axonal boutons forming connections with dendritic spines. Visual stimulation after dark rearing during the critical period causes a rapid increase in the number of pERK-labelled synapses in cortical layers I–II/III. This visually-induced activation of ERK at synaptic sites occurs in pre- and post-synaptic compartments and its temporal profile is identical to that of ERK activation in neuronal cell bodies. CONCLUSIONS/SIGNIFICANCE: Visual stimulation in vivo increases pERK expression at pre- and post-synaptic sites of axo-spinous junctions, suggesting that ERK plays an important role in the local modulation of synaptic function. The data presented here support a model in which pERK can have early and late actions both centrally in the cell nucleus and peripherally at synaptic contacts.